Radiographic assessment of the skeletons of Dolly and other clones finds no abnormal osteoarthritis - Corr, Sandra A.; Gardner, David S.; Langley-Hobbs, Sorrel; Ness, Malcolm G.; Kitchener, Andrew C.; Sinclair, Kevin D. (Nature Publishing Group, 2017)
Our recent report detailing the health status of cloned sheep concluded that the animals had aged normally. This is in stark contrast to reports on Dolly (first animal cloned from adult cells) whose diagnoses of osteoarthritis (OA) at 5½ years of age led to considerable scientific concern and media debate over the possibility of early-onset age-related diseases in cloned animals. Our study included four 8-year old ewes derived from the cell line that gave rise to Dolly, yet none of our aged sheep showed clinical signs of OA, and they had radiographic evidence of only mild or, in one case, moderate OA. Given that the only formal record of OA in Dolly is a brief mention of a single joint in a conference abstract, this led us to question whether the original concerns about Dolly’s OA were justified. As none of the original clinical or radiographic records were preserved, we undertook radiographic examination of the skeletons of Dolly and her contemporary clones. We report a prevalence and distribution of radiographic-OA similar to that observed in naturally conceived sheep, and our healthy aged cloned sheep. We conclude that the original concerns that cloning had caused early-onset OA in Dolly were unfounded.